Campuzano Herrera, Yuliana Stefania(2023)IMPORTANCIA DE LOS NUTRIENTES PRIMARIOS EN EL DESARROLLO DE PLÁNTULAS DE BANANO CULTIVAR WILLIAMS A NIVEL DE VIVERO.Quevedo.UTEQ.66p. - Campuzano Herrera, Yuliana Stefania (2023)
The present research was aimed at using Bioinformatics to study metabolic pathways related to resistance by aluminum and cadmium pollution in cocoa (Theobroma cacao L.) cultivation. The study was carried out at the Campus Experimental “La María”, Facultad de Ciencias Pecuarias y Biológicas, belonging to the Universidad Técnica Estatal de Quevedo, located at kilometer 7.5 of the Quevedo - El Empalme road, San Felipe Campus, Canton Mocache, To compare the sequenced cacao genomes with other species of the Malvaceae and the metallophytes in order to reveal genomic data related to genetic factors in the evolutionary processes of both species, additionally to characterize and elucidate in silico family of genes, transcription factors and protein related heavy metal effects various softwares available for free on the web will be used. The results were filtered by Evaluate cutoff 10E-10. PlantTFcat is a tool to analyze the identification and categorization of TF/TR/CR plant genes at the genomic scale.